Թուրքական գյոքալփագիտության պատմությունից - Ա. Վ. Սաֆարյան (ՀՀ ԳԱԱ հրատ.)
И в Турции, и на Западе периодически публикуются работы турецких социологов, историков, философов, литературоведов, лингвистов, культурологов, посвященные жизни, политической и педагогической деятельности, а также поэзии виднейшего идеолога тюркизма (тюркизма и пантюркизма) З. Я. Гекалпу (1876-1924) и, в частности, фундаментальному труду “Основы тюркизма” (1923). Works of Turkish sociologists, historians, philosophers, philologists, linguists and culture experts devoted to the biography, political and pedagogical activities as well as to the poetry of the most famous ideologist of Türkçülük (Türkiyecilik ve Turancılık) Ziya Gökalp and his fundamental work “The Principles of Turkism” are periodically published in Turkey and in the West.
Keywords: History; Political Science; Modern History; D History; J Political Science